Saving for the future: extending the consensus on workplace pensions - Harrop, Andrew; Hall, Sam (London, 2017)
"With the government due to report on its review of automatic enrolment this month, sparking fresh debate about workplace pensions, a new report brings together politicians from across the political divide and leading thinkers to set out ideas for the next stage of workplace pension reform.